Drug Information Centre (DIC)-An Indian Scenario - Chauhan, Nitesh S; F, Firdous; Raveendra, R; J, Geetha; Gopalakrishna, B; Karki, Roopa (Indian Journal of Pharmacy Practice)
Drug information centre refer to facility specially set aside for, and specializing in the provision of drug information & related issues. The purpose of drug information centre is to provide authentic individualized, accurate, relevant and unbiased drug information to the consumers and healthcare professionals regarding medication related inquiries to the nation for health care & drug safety aspects by answering their call regarding the all critical problems on dug information, their uses and their side effects. Apart from that the centre also provides in-depth, impartial source of crucial drug information to meet the needs of the practicing physicians, pharmacists and other health care professionals to safeguard the health, financial and legal interests of the patient & to broaden the pharmacist role visible in the society & community. Number of drug information centers are being opened with the prospective of safe health care & drug safety which will surely serve the community & enhanced the role of community pharmacist. Information present in the current paper will not only enlighten the role of drug information centre but also focused on the rational use of drug
Keywords: Drug information; health care